Nitrogen application in soil and foliar spray with urea and gibberelic acid in Setária anceps stapf cv. Kazungula - Favoretto, Vanildo; Zanetti, Pedro Antonio do Nascimento; Reis, Ricardo Andrade; Vieira, Paulo de Figueiredo (Pesquisa Agropecuaria Brasileira, 2014)
The purpose of the experiment was to study the effects of split applications of mineral nitrogen during the wet season combined with foliar applications of urea and/or gibberellic acid on the production and quality of Setaria anceps Stapf cv. Kazungula. Nitrogen (60 kg/ha/year) was applied according to the following treatments: No nitrogen, N20M40 (20kg N/ha in November +40kg N/ha in March), N30M30 (30 kg N/ha in November + 30 kg N/ha in March) and F20M40 (20 kg N/ha in February + 40 kg N/ha in March). In dry season, four foliar applications were tested: Control (no gibberellic acid or urea), urea at 2%, gibberellic acid at 50 ppm, and urea at 2% + gibberellic acid at 50 ppm. Data obtained show that split application of nitrogen was not enough to increase dry-matter production of Setaria grass in the wet season, although the dry-matter increased during dry season. Setaria showed a good distribution of dry-matter production between wet and dry season, presenting in the latter 34.52% of annual production. Foliar applications did not affect dry-matter production and chemical composition of the different parts of the plants during dry season.